(3GdeRjMajIs - (3CHh YHOGHHg eMeO Hf CMeO Hf YeQ CHj GdSYhO GdNRGYj GdeRjMajs ((3eOjfI RHjO s)
(3ChdgG (B:s
(3GdMeO GdPi SWM GdCQV hegO CeG HYO aEfi deG QCjJ YOe GdaQGZ hbdI GdETJZGd eY fTGW YGeI GdcJGH Edi eYQaI Yde Gd MSGH , YQV HNWGQi Cf CSfY ebOeI ai Yde eNGQL GdcShQ s
(3BNQgG (B:s
(3aEf bGd eG dGf hKdK eGd ajchf GdLPQ KdGKI hGdeGd JSYI aCage Pdc JUH Ef TGA Gddg JYGdi hGdMeO ddg QH GdYGdejf JeJ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B195 - (3U(B211s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQCgG MSf Hf CMeO GdMLOQi Ydi TjNg Uai GdOjf CMeO Hf YHO dGdg GdTbO ai GdSfI faSgG s
(3cJHJ HYV cdeGJ GdfSNI HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdQjGVjGJs